Parenting Challenges and Reasons for Not Availing Rehabilitation Services Among Families of Adolescents with Autism Spectrum Disorder: A Qualitative Study. Issue 3 (May 2023) - Noori, Fathima; Tiwari, Shivani; Padickaparambil, Sebastian; Pothiyil, Dan Isaac
Background: Autism spectrum disorder (ASD) is a lifelong condition requiring continued rehabilitation services. However, children with ASD who seek rehabilitation services tend to drop out once they enter puberty, because of varying reasons, some of which are unknown. This study intended to explore the reasons for not availing of rehabilitation services in families of adolescents with ASD and the parental challenges in taking care of adolescents with ASD. Method: The study followed a descriptive qualitative research design by conducting in-depth interviews with 12 primary caregivers of adolescents with ASD (10 to 19 years; mean age 16.3 years) who were not availing of any direct rehabilitation services. All interviews were conducted by telephone, and data obtained were subjected to thematic analysis. Results: The results showed two major themes, viz. reasons for discontinuing the rehabilitation services and parental challenges among primary caregivers of adolescents with ASD, and their corresponding subthemes. The reasons for discontinuation of rehabilitation included financial difficulties, difficulties in handling the child, and a lack of improvement in the child. A few of the parental challenges were disruptive behaviors and associated medical conditions of the child and difficulty in managing changes during adolescence. Conclusion: The study revealed several reasons as well as potential barriers to avail rehabilitation services in Indian families of adolescents with ASD. The data further unveil related parenting challenges specific to the Indian context. Further, implications for service providers and policymakers are discussed.